Correction of pseudoexon splicing caused by a novel intronic dysferlin mutation. Issue 4 (3rd March 2019) - Dominov, Janice A.; Uyan, Özgün; McKenna‐Yasek, Diane; Nallamilli, Babi Ramesh Reddy; Kergourlay, Virginie; Bartoli, Marc; Levy, Nicolas; Hudson, Judith; Evangelista, Teresinha; Lochmuller, Hanns; Krahn, Martin; Rufibach, Laura; et al.
Abstract: Objective: Dysferlin is a large transmembrane protein that functions in critical processes of membrane repair and vesicle fusion. Dysferlin‐deficiency due to mutations in the dysferlin gene leads to muscular dystrophy (Miyoshi myopathy (MM), limb girdle muscular dystrophy type 2B (LGMD2B), distal myopathy with anterior tibial onset (DMAT)), typically with early adult onset. At least 416 pathogenic dysferlin mutations are known, but for approximately 17% of patients, one or both of their pathogenic variants remain undefined following standard exon sequencing methods that interrogate exons and nearby flanking intronic regions but not the majority of intronic regions. Methods: We sequenced RNA from myogenic cells to identify a novel dysferlin pathogenic variant in two affected siblings that previously had only one disease‐causing variant identified. We designed antisense oligonucleotides (AONs) to bypass the effects of this mutation on RNA splicing. Results: We identified a new pathogenic point mutation deep within dysferlin intron 50i. This intronic variant causes aberrant mRNA splicing and inclusion of an additional pseudoexon (PE, we term PE50.1) within the mature dysferlin mRNA. PE50.1 inclusion alters the protein sequence, causing premature translation termination. We identified this mutation in 23 dysferlinopathy patients (seventeen families), revealing it to be one of the more prevalent dysferlin mutations. We used AON‐mediated exon skipping to correct the aberrant PE50.1 splicing events in vitro, which increased normal mRNA production and significantly restored dysferlin protein expression. Interpretation: Deep intronic mutations can be a common underlying cause of dysferlinopathy, and importantly, could be treatable with AON‐based exon‐skipping strategies.